People’s Participation in Local Governance of Besishahar Municipality of Lamjung District in Western Nepal - Dahal, Girdhari (Tribhuvan University Journal, 2022)
The key aim of this article is to look into the current state of people’s participation and immersion in local governance of Besishahar Municipality of Lamjung district. Outlined by purposive non-probability judgmental sampling techniques, qualitative data saturation procedure was adopted so that to make valid understanding of local governance and fifteen sample respondents were ascertained. Elected officials, Mayor, Vice Mayor, intellectuals, and government officer, Ward members, intellectuals, and public workers were among the 15 respondents. Primary data was accumulated mainly through formal and informal field and telephonic interviews. The study findings deduced that people’s lively participation in many areas of government and development activities at the local level has been progressive and encouraging. The legislature plays a significant role in Municipality assembly lawmaking and the executive body’s primary responsibility is to provide day-to-day service delivery to the people at the local level. However, there are numerous problems and possibilities. They lack the necessary resources and budget for social and economic development. Amid tribulations, the number of elected representatives has made altogether seventy-one local laws. Local governments have 22 rights under the Nepalese constitution of 2015. At this juncture, they can start building capability at the grassroots level. The local government can help them develop their leadership skills. Broadly, amidst shortcomings, prospects and challenges, this Municipality’s innovative works in social, political, and economic development through infrastructural operations are commendable.